A Sec63p-BiP complex from yeast is required for protein translocation in a reconstituted proteoliposome (The Rockefeller University Press, 1993)
Reconstituted proteoliposomes derived from solubilized yeast microsomes are able to translocate a secreted yeast mating pheromone precursor (Brodsky, J. L., S. Hamamoto, D. Feldheim, and R. Schekman. 1993. J. Cell Biol. 120:95-107). Reconstituted proteoliposomes prepared from strains with mutations in the SEC63 or KAR2 genes are defective for translocation; the kar2 defect can be overcome by the addition of purified BiP (encoded by the KAR2 gene). We now show that addition of BiP to wild-type reconstituted vesicles increases their translocation efficiency three-fold. To identify other ER components that are required for translocation, we purified a microsomal membrane protein complex that contains Sec63p. We found that the complex also includes BiP, Sec66p (gp31.5), and Sec67p (p23). The Sec63p complex restores translocation activity to reconstituted vesicles that are prepared from a sec63-1 strain, or from cells in which the SEC66 or SEC67 genes are disrupted. BiP dissociates from the complex when the purification is performed in the presence of ATP gamma S or when the starting membranes are from yeast containing the sec63-1 mutation. We conclude that the purified Sec63p complex is active and required for protein translocation, and that the association of BiP with the complex may be regulated in vivo.